2010
DOI: 10.1093/pasj/62.4.951
|View full text |Cite
|
Sign up to set email alerts
|

Mass Estimation of Merging Galaxy Clusters

Abstract: We investigate the impact of mergers on the mass estimation of galaxy clusters using N-body + hydrodynamical simulation data. We estimate virial mass from these data and compare it with real mass. When the smaller subcluster's mass is larger than a quarter of that of the larger one, virial mass can be larger than twice of the real mass. The results strongly depend on the observational directions, because of anisotropic velocity distribution of the member galaxies. We also make the Xray surface brightness and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…These values may be closer to the real values than those estimated from the galaxy velocity dispersions, since e.g. Takizawa et al (2010) found that for merging clusters X-ray derived masses were usually more reliable than virial mass estimations. However, as explained for example by Nagai et al (2007), although the total ICM mass can be measured quite accurately (to better than ∼6%) in clusters, the hydrostatic estimate of the gravitationally bound mass is biased low by about 5−20% throughout the virial region, primarily due to additional pressure support provided by subsonic bulk motions in the ICM, ubiquitous in our simulations even in relaxed systems.…”
Section: Search For Gravitationally Bound Structuresmentioning
confidence: 56%
“…These values may be closer to the real values than those estimated from the galaxy velocity dispersions, since e.g. Takizawa et al (2010) found that for merging clusters X-ray derived masses were usually more reliable than virial mass estimations. However, as explained for example by Nagai et al (2007), although the total ICM mass can be measured quite accurately (to better than ∼6%) in clusters, the hydrostatic estimate of the gravitationally bound mass is biased low by about 5−20% throughout the virial region, primarily due to additional pressure support provided by subsonic bulk motions in the ICM, ubiquitous in our simulations even in relaxed systems.…”
Section: Search For Gravitationally Bound Structuresmentioning
confidence: 56%
“…As shown by e.g. Takizawa, Nagino & Matsushita (2010), even mass estimates for spherical X-ray systems are not always recovered well. Recent simulations by Nelson et al (2011) have investigated in detail the evolution of the non-thermal support bias as a function of radius and of the merger stage.…”
Section: (I) X-ray and Weak-lensing Massesmentioning
confidence: 98%
“…We summarize these subcluster properties in Table 3. We use the biweight analysis to mitigate outliers from affecting the estimates of the velocity dispersion and redshift, but this does not protect against the well known fact that mergers tend to bias high the velocity dispersion based mass estimates (Takizawa, Nagino & Matsushita 2010;Saro et al 2013). We discuss this in more detail in §6.3.…”
Section: Mcmc-gmm Analysismentioning
confidence: 99%